DIFFERENTIATED TASKS FOR MIXED-ABILITY CLASSROOMS - Hasibuan, Kalayo; Reosta Ayu, Ica; Oktaviani, Rizka; Eka Syaputra, Ilham; Febrian, Kevin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mixed-ability classrooms are commonly found in educational settings where students possess different levels of knowledge, learning speed, motivation, and language proficiency. These differences often create challenges for teachers in delivering effective instruction that can accommodate all learners equally. One strategy that can be implemented to address this issue is differentiated tasks. Differentiated tasks refer to learning activities designed according to students’ readiness, interests, and learning styles so that every student can participate actively in the learning process. This paper discusses the implementation of differentiated tasks in mixed-ability classrooms and their impact on student engagement and learning outcomes. The study uses a descriptive qualitative method by reviewing related literature and analyzing classroom practices. The findings show that differentiated tasks help teachers provide fair learning opportunities, improve student participation, and reduce learning gaps among students. In addition, students become more motivated and confident because the tasks are adjusted to their abilities. However, teachers also face challenges such as time management, classroom organization, and the need for creativity in preparing learning materials.